Gag-Positive Reservoir Cells Are Susceptible to HIV-Specific Cytotoxic T Lymphocyte Mediated Clearance In Vitro and Can Be Detected In Vivo - Graf, Erin H.; Pace, Matthew J.; Peterson, Bennett A.; Lynch, Lindsay J.; Chukwulebe, Steve B.; Mexas, Angela M.; Shaheen, Farida; Martin, Jeffrey N.; Deeks, Steven G.; Connors, Mark; Migueles, Stephen A.; O’Doherty, Una (PLOS ONE, 2013)
Resting CD4+ T cells infected with HIV persist in the presence of suppressive anti-viral therapy (ART) and are barriers to a cure. One potential curative approach, therapeutic vaccination, is fueled by recognition of the ability of a subset of elite controllers (EC) to control virus without therapy due to robust anti-HIV immune responses. Controllers have low levels of integrated HIV DNA and low levels of replication competent virus, suggesting a small reservoir. As our recent data indicates some reservoir cells can produce HIV proteins (termed GPR cells for Gag-positive reservoir cells), we hypothesized that a fraction of HIV-expressing resting CD4+ T cells could be efficiently targeted and cleared in individuals who control HIV via anti-HIV cytotoxic T lymphocytes (CTL). To test this we examined if superinfected resting CD4+ T cells from EC express HIV Gag without producing infectious virus and the susceptibility of these cells to CTL. We found that resting CD4+ T cells expressed HIV Gag and were cleared by autologous CD8+ T cells from EC. Importantly, we found the extent of CTL clearance in our in vitro assay correlates with in vivo reservoir size and that a population of Gag expressing resting CD4+ T cells exists in vivo in patients well controlled on therapy.